2006
DOI: 10.1038/nature04815
|View full text |Cite
|
Sign up to set email alerts
|

A PHD finger of NURF couples histone H3 lysine 4 trimethylation with chromatin remodelling

Abstract: Lysine methylation of histones is recognized as an important component of an epigenetic indexing system demarcating transcriptionally active and inactive chromatin domains. Trimethylation of histone H3 lysine 4 (H3K4me3) marks transcription start sites of virtually all active genes. Recently, we reported that the WD40-repeat protein WDR5 is important for global levels of H3K4me3 and control of HOX gene expression. Here we show that a plant homeodomain (PHD) finger of nucleosome remodelling factor (NURF), an IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
902
3
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,052 publications
(928 citation statements)
references
References 28 publications
21
902
3
2
Order By: Relevance
“…The presence of such an epitope was found to be essential in generating ATP-dependent regularly spaced nucleosome arrays by RSF [141]. Recent reports have shown that H3K9me3 mark can actively recruit the PHD domain of NURF [142,143]. Similarly, the same mark was also shown to recruit Isw1p ATPase to chromatin [144].…”
Section: Role Of Histone Tails and Their Modification In Chromatin Rementioning
confidence: 99%
“…The presence of such an epitope was found to be essential in generating ATP-dependent regularly spaced nucleosome arrays by RSF [141]. Recent reports have shown that H3K9me3 mark can actively recruit the PHD domain of NURF [142,143]. Similarly, the same mark was also shown to recruit Isw1p ATPase to chromatin [144].…”
Section: Role Of Histone Tails and Their Modification In Chromatin Rementioning
confidence: 99%
“…PHD fingers may also function as methyl-lysine-binding modules. One PHD finger of NURF recognizes trimethyl lysine 4 of histone H3 to couple ATP-dependent chromatin remodeling to histone methylation Wysocka et al, 2006), and the PHD finger of ING2 binds to the same mark to stimulate methylation-dependent deacetylation (Pena et al, 2006;Shi et al, 2006). Moreover, methylation of histone H3 at lysine 4 promotes association with yeast Yng1, a subunit of the NuA3 acetyltransferase complex (Martin et al, 2006;Taverna et al, 2006).…”
Section: Moz and Morf As Catalytic Subunits Of Quartet Complexesmentioning
confidence: 99%
“…Confirm specific association of the identified protein with the modified peptide by immunoblotting eluates with specific antibodies, if available, and by performing pull-down assays using purified recombinant protein as input (for examples, see: [8,9]). …”
Section: Peptide Pull-down Assay From Nuclear Extractsmentioning
confidence: 99%
“…The protocol described here calls for washes with buffer containing 300mM salt, which usually result in relatively low backgrounds in pull-downs and do not disrupt association of HP1, WDR5, BPTF or CBX7 with H3 peptides [8,9,14]. However, salt concentration of 250 mM disrupts association of NuRD complex with H3 peptides [10].…”
Section: Optimizing Washing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation